A regulative norms mining algorithm for complex adaptive system - Mahmoud M.A.; Ahmad M.S.; Yusoff M.Z.M.; Mostafa S.A. (Springer Verlag, 2023)
Adaptive systems; Soft computing; Complex adaptive systems; Exceptional events; Mining algorithms; Normative system; Norms identifications; Regulative norms; Social norm; Data mining